Expression of microfold (M) cells in 3D co-culture models towards propagation of human norovirus / Mizanurfakhri Ghazali - Ghazali, Mizanurfakhri (2023)
Microfold (M) cells are specialised cells of the intestinal follicular associated epithelium (FAE) in Peyer's patches. The M cells play crucial role in initiating immune responses within the mucosa-associated lymphoid tissue and transcytosis of particles such as antigen and bacteria from the apical side into the dome-like structure of lymphocytes in the basolateral region of the intestinal epithelium. As an enteric virus, human norovirus (HuNoV) has been proposed to invade host cells by exploiting the formation of M cells as it breaches the human intestinal epithelium. Although HuNoV infections cause an estimated 200,000 deaths per year worldwide, HuNoV remains poorly characterised due to the lack of a reliable and reproducible cell culture system for its replication. Therefore, this study aims to develop three-dimensional (3D) culture models expressing the M cells to accommodate HuNoV replication. The 3D culture model comprised of colon carcinoma cells and lymphocytes, co-cultivated on two separate systems; the Transmembrane well plate and alginate hydrogel beads (Alcart©). The integrity and permeability of the cell monolayer were measured as transepithelial electric resistance (TEER) whereby the highly polarised and dense Caco-2 monolayer showed high TEER value that decreased after co-culture with Raji B cells. Scanning electron microscopy (SEM) of the Caco-2 monoculture showed a dense brush border structure, indicating well-distributed microvilli, while both 3D co-culture models showed a sparse and truncated cell structure with clear appearance of a reduced apical surface in the hydrogel beads-entrapping model. Expression of the M cells was further confirmed by immunocytochemistry and Western blot analysis, whereby the expression of alpha-5 protein was highest in the Transmembrane co-culture compared with the Alcart© bead co-culture. On the other hand, beta-1 protein expression was reduced in both 3D co-culture when compared with the monoculture. Interestingly, sialyl Lewis A antigen (CA19-9) was not expressed in either model. Meanwhile, due to lack of HuNoV fresh isolates, this study used a molecular cloning technique to construct a synthetic virus (sHuNoV), to be propagated in both M cells 3D co-culture models. The gene recombinant strategy comprised of digestion and ligation of cDNA fragments into several plasmid vectors. However, various problems hindered the insertion of the fragments into the vectors, resulting in the unsuccessful recombinant DNA plasmid. Consequently, work on in vitro transcription and translation of sHuNoV could not proceed. Nevertheless, this study concludes that 3D co-culture models support the formation of M cells, which have high potential for further development in HuNoV propagation.